Cannabinoid Attenuation of Intestinal Inflammation in Chronic SIV-Infected Rhesus Macaques Involves T Cell Modulation and Differential Expression of Micro-RNAs and Pro-inflammatory Genes - Kumar, Vinay; Torben, Workineh; Mansfield, Joshua; Alvarez, Xavier; Vande Stouwe, Curtis; Li, Jian; Byrareddy, Siddappa N.; Didier, Peter J.; Pahar, Bapi; Molina, Patricia E.; Mohan, Mahesh (Frontiers in Immunology, 2019)
Cannabis use is frequent in HIV-infected individuals for its appetite stimulation and anti-inflammatory effects. To identify the underlying molecular mechanisms associated with these effects, we simultaneously profiled micro-RNA (miRNA) and mRNA expression in the colon of chronically simian immunodeficiency virus (SIV)-infected rhesus macaques administered either vehicle (VEH/SIV; n=9) or Δ9- tetrahydrocannabinol (Δ9-THC; THC/SIV; n=8). Proinflammatory miR-130a, miR-222 and miR-29b, lipopolysaccharide-responsive miR-146b-5p and SIV-induced miR-190b were significantly upregulated in VEH/SIV rhesus macaques. Compared to VEH/SIV rhesus macaques, 10 miRNAs were significantly upregulated in THC/SIV rhesus macaques, among which miR-204 was confirmed to directly target MMP8, an extracellular matrix-degrading collagenase that was significantly downregulated in THC/SIV rhesus macaques. Moreover, THC/SIV rhesus macaques failed to upregulate proinflammatory miR-21, miR-141 and miR-222, and alpha/beta-defensins, suggesting attenuated intestinal inflammation. Further, THC/SIV rhesus macaques showed higher expression of tight junction proteins (occludin, claudin-3), anti-inflammatory MUC13, keratin-8 (stress protection), PROM1 (epithelial proliferation) and anti-HIV CCL5. Gomori one-step trichrome staining detected significant collagen deposition (fibrosis) in the paracortex and B cell follicular zones of axillary lymph nodes from all VEH/SIV but none of the THC/SIV rhesus macaques, thus demonstrating the ability of Δ9-THC to prevent lymph node fibrosis, a serious irreversible consequence of HIV induced chronic inflammation. Furthermore, using flow cytometry, we showed that Δ9-THC suppressed intestinal T cell proliferation/activation (Ki67/HLA-DR) and PD-1 expression and increased the percentages of anti-inflammatory CD163+ macrophages. Finally, while Δ9-THC did not affect the levels of CD4+ T cells, it significantly reduced absolute CD8+ T cell numbers in peripheral blood at 150 and 180 days post-SIV infection. These translational findings strongly support a role for differential miRNA/gene induction and T cell activation in Δ9-THC-mediated suppression of intestinal inflammation in HIV/SIV and potentially other chronic inflammatory diseases of the intestine.